PENERAPAN FUZZY MAMDANI PADA PENILAIAN KINERJA DOSEN (STUDI KASUS STMIK KAPUTAMA BINJAI) - Simajuntak, Magdalena; Fauzi, Achmad (Journal Information System Development (ISD), 2017)
This research is aimed to apply Mamdani Method to get function optimization value quickly in lecturer performance assessment. Input consists of 3 (three) variables are: Variable Material, Variable Discipline and Attitude Variables. The results obtained in this study the value of function that has been optimized which will get the best lecturer in performance. Keywords: Mamdani, Optimization